2006
DOI: 10.1255/jnirs.686
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Total Carbon and Nitrogen Content in a Range of Tropical Soils Using near Infrared Spectroscopy: Influence of Replication and Sample Grinding and Drying

Abstract: Near infrared (NIR) refl ectance spectroscopy has been receiving increased attention for the rapid and inexpensive determination of soil properties and of total carbon (Ct) and nitrogen content (Nt) in particular. However, methodological aspects such as sample grinding and drying or replication have not been addressed extensively. The objectives of the paper were, thus, to assess how NIR predictions of Ct and Nt were affected by sample grinding (2 mm sieving vs. 0.2 mm grinding), drying (air-drying vs oven-dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 27 publications
5
57
1
1
Order By: Relevance
“…The calibration performances for organic carbon and total nitrogen obtained during this study (R 2 = 0.91 and 0.92 for carbon and nitrogen, respectively) were of the same order of magnitude as those obtained by Barthès et al (2006) with 0.94 and 0.92 for carbon and nitrogen, respectively and Brunet et al (2007) with 0.91 and 0.87 for carbon and nitrogen, respectively. These two studies were carried out on a large range of tropical sandy and clayey soils with similar sample treatments: 2 mm sieving, two repetitions on the same sample and using a first order derivative for regressions.…”
Section: Nir Spectra and Prediction Of Soil Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…The calibration performances for organic carbon and total nitrogen obtained during this study (R 2 = 0.91 and 0.92 for carbon and nitrogen, respectively) were of the same order of magnitude as those obtained by Barthès et al (2006) with 0.94 and 0.92 for carbon and nitrogen, respectively and Brunet et al (2007) with 0.91 and 0.87 for carbon and nitrogen, respectively. These two studies were carried out on a large range of tropical sandy and clayey soils with similar sample treatments: 2 mm sieving, two repetitions on the same sample and using a first order derivative for regressions.…”
Section: Nir Spectra and Prediction Of Soil Propertiessupporting
confidence: 79%
“…NIRS is a non-destructive physical analysis method that is used extensively to predict soil organic properties, particularly total carbon and total nitrogen (e.g., Dalal and Henry, 1986;Morra et al, 1991;He et al, 2005;Barthès et al, 2006;Brunet et al, 2007). Other properties linked to organic matter (OM) may also be predicted, such as the carbon and nitrogen concentrations in particle size fractions , cation exchange capacity (CEC), water content, metal content (e.g., Fe, Cu, Zn), or soil texture (Chang et al, 2001(Chang et al, , 2005Chang and Laird, 2002;Morón and Cozzolino, 2003;Vergnoux et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fystro (2002) found a slightly increased prediction error for organic carbon and total nitrogen using air-dry, ball-milled (<0.5 mm) soil compared with coarse (<4 mm) soil, as did Russell (2003) for soil treated in a puck and ring grinder compared with soil crushed and sieved through 2 mm. Barthes et al (2006), on the other hand, reported a positive result of grinding (<0.2 mm) compared with sieving soil (<2 mm). They suggested that the contradictory results were due to different responses to grinding between aggregated clay soils and single-grain, coarse-textured soils, as crushing clay aggregates would produce more homogeneous samples.…”
Section: Sample Pretreatmentmentioning
confidence: 96%
“…Each sample comprised 1.5 kg of soil collected from 6-7 sub-samples on a radius of 2.5 m from the reference position, at a standard 0.3 m depth. Total nitrogen (as a result of N available at the beginning of the cycle plus N mineralized from organic matter) was determined based on Near Infrared Spectroscopy (NIR) [10]. Data underwent a standard resampling weighted on a nearest-neighbor weighted function, in order to allow realization of a homogeneous map over the experimental field (Figures 1-1 and 1-2).…”
Section: Discussionmentioning
confidence: 99%